Benefit of Physiologically Variable Over Pressure-Controlled Ventilation in a Model of Chronic Obstructive Pulmonary Disease: A Randomized Study - Dos Santos Rocha, Andre; Südy, Roberta; Bizzotto, Davide; Kassai, Miklos; Carvalho, Tania; Dellacà, Raffaele L.; Peták, Ferenc; Habre, Walid (Frontiers in Physiology, 2021)
Introduction The advantages of physiologically variable ventilation (PVV) based on a spontaneous breathing pattern have been demonstrated in several respiratory conditions. However, its potential benefits in chronic obstructive pulmonary disease (COPD) have not yet been characterized. We used an experimental model of COPD to compare respiratory function outcomes after 6 h of PVV versus conventional pressure-controlled ventilation (PCV). Materials and Methods Rabbits received nebulized elastase and lipopolysaccharide throughout 4 weeks. After 30 days, animals were anesthetized, tracheotomized, and randomized to receive 6 h of physiologically variable (n = 8) or conventional PCV (n = 7). Blood gases, respiratory mechanics, and chest fluoroscopy were assessed hourly. Results After 6 h of ventilation, animals receiving variable ventilation demonstrated significantly higher oxygenation index (PaO2/FiO2 441 ± 37 (mean ± standard deviation) versus 354 ± 61 mmHg, p < 0.001) and lower respiratory elastance (359 ± 36 versus 463 ± 81 cmH2O/L, p < 0.01) than animals receiving PCV. Animals ventilated with the variable mode also presented less lung derecruitment (decrease in lung aerated area, –3.4 ± 9.9 versus –17.9 ± 6.7%, p < 0.01) and intrapulmonary shunt fraction (9.6 ± 4.1 versus 17.0 ± 5.8%, p < 0.01). Conclusion PVV applied to a model of COPD improved oxygenation, respiratory mechanics, lung aeration, and intrapulmonary shunt fraction compared to conventional ventilation. A reduction in alveolar derecruitment and lung tissue stress leading to better aeration and gas exchange may explain the benefits of PVV.